An Experimental Study on Vortex-Induced Vibration Suppression of a Long Flexible Catenary Cable by Using Vibration Dampers - Li Ruan; Hongzhong Zhu; Changhong Hu (Journal of Marine Science and Engineering)
In this paper, an experimental study is conducted to investigate the effectiveness of vibration dampers in suppressing vortex-induced vibration in a long, flexible catenary cable with a low mass ratio. The dampers, consisting of two small, symmetric, lightweight pipes clamped to the cable, are sparsely deployed along the cable to shape the vibration characteristics. The experimental results demonstrate that dampers significantly reduce the vibration amplitude by up to 60% and axial tension by up to 61% at high flow velocities, effectively suppressing the cable vibration in perpendicular flow. In addition, it is observed that the in-line and cross-flow vibration frequencies are approximately equal when the dampers are applied. This behavior contrasts with the conventional undamped catenary cable, where the in-line vibration frequencies are double those of the cross-flow frequencies.